Stress Response and Hearing Loss Differentially Contribute to Dynamic Alterations in Hippocampal Neurogenesis and Microglial Reactivity in Mice Exposed to Acute Noise Exposure - Li, Qian; Li, Hong; Yao, Xiuting; Wang, Conghui; Liu, Haiqing; Xu, Dan; Yang, Chenxi; Zhuang, Hong; Xiao, Yu; Liu, Rui; Shen, Sinuo; Zhou, Shaoyang; et al. (Frontiers in Neuroscience, 2021)
Noise-induced hearing loss (NIHL) is one of the most prevalent forms of acquired hearing loss, and it is associated with aberrant microglial status and reduced hippocampal neurogenesis; however, the nature of these associations is far from being elucidated. Beyond its direct effects on the auditory system, exposure to intense noise has previously been shown to acutely activate the stress response, which has increasingly been linked to both microglial activity and adult hippocampal neurogenesis in recent years. Given the pervasiveness of noise pollution in modern society and the important implications of either microglial activity or hippocampal neurogenesis for cognitive and emotional function, this study was designed to investigate how microglial status and hippocampal neurogenesis change over time following acoustic exposure and to analyze the possible roles of the noise exposure-induced stress response and hearing loss in these changes. To accomplish this, adult male C57BL/6J mice were randomly assigned to either a control or noise exposure (NE) group. Auditory function was assessed by measuring ABR thresholds at 20 days post noise exposure. The time-course profile of serum corticosterone levels, microglial status and hippocampal neurogenesis during the 28 days following noise exposure were quantified by ELISA or immunofluorescence staining. Our results illustrated a permanent moderate-to-severe degree of hearing loss, an early but transient increase in serum corticosterone levels, and time-dependent dynamic alterations in microglial activation status and hippocampal neurogenesis, which both present an early but transient change and a late but enduring change. These findings provide evidence that both the stress response and hearing loss contribute to the dynamic alterations of microglia and hippocampal neurogenesis following noise exposure; moreover, noise-induced permanent hearing loss rather than noise-induced transient stress is more likely to be responsible for perpetuating the neurodegenerative process associated with many neurological diseases.